Medication Access & Adherence - MIDWEST SAPH 2018 (University of Minnesota Libraries Publishing, 2018)
Faculty Discussant: Olayinka Shiyanbola, PhD Article 1: The Association Between Adverse Drug Reaction Incidence and Drug Adherence : A Systematic Approach Huang CY; Villa KR;Dircksen, K; Sabbaghi A; Murawski MM Article 2: Adherence to Biologic and Conventional Disease Modifying Anti-Rheumatic Drugs in Patients with Rheumatoid Arthritis Pragya Mishra, MS, PhD Candidate; Joseph Thomas III, PhD, Professor Article 3: Cost-Effectiveness of a Theoretical Pharmacist-Led Breast Cancer Adherence Intervention Alemseged Ayele Asfaw, MSc; Brian Talon, PharmD; Scott Wirth PharmD, BCOP; Lisa Sharp PhD; Daniel Touchette PharmD, MA Article 4: Antidiabetic Drug Adherence among Childless Adults Experiencing Medicaid Coverage Expansion in Wisconsin Nam Hyo Kim, MS; Kevin A. Look, PhD; Marguerite Burns, PhD Article 5: Exploring the Barriers and Facilitators of Medication Adherence in Patients with Type 2 Diabetes across Different Health Literacy Levels Yen-Ming Huang, MS; Olayinka O. Shiyanbola, PhD BPharm Article 6: Closing the Medicare Part D Coverage Gap: Impact on Out-Of-Pocket Burden, Drug Utilization, and Access to Care among Beneficiaries and Those with Cancer Joohyun Park, MS; Kevin A. Look, PharmD, PhD Article 7: Relationship of Travel Distance and Time to Dispensing Pharmacies on Warfarin Control in an Urban Population Connie H. Yan, PharmD; Edith Nutescu, PharmD, MS; Lisa K. Sharp, PhD